2016
DOI: 10.1007/s00441-016-2395-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124 is differentially expressed in derivatives of the sympathoadrenal cell lineage and promotes neurite elongation in chromaffin cells

Abstract: The neural-crest-derived sympathoadrenal cell lineage gives rise to sympathetic neurons and to endocrine chromaffin cells of the adrenal medulla. Both cell types express a largely overlapping set of genes, including those coding for the molecular machinery related to the synthesis and exocytotic release of catecholamines. During their early development, sympathetic neurons and chromaffin cells rely on a shared transcription factor network that controls the establishment of these common features. Despite many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…(Stubbusch, et al, 2013). One such microRNA, miRNA 124, is present in sympathetic mouse neuroblasts and causes neurite elongation when over-expressed in cultured chromaffin cells and is up-regulated during the induction of neurites by NGF in PC12 cells (Shtukmaster, et al, 2016).…”
Section: Differentiation Of Sympathetic Neuroblasts From Nccmentioning
confidence: 99%
“…(Stubbusch, et al, 2013). One such microRNA, miRNA 124, is present in sympathetic mouse neuroblasts and causes neurite elongation when over-expressed in cultured chromaffin cells and is up-regulated during the induction of neurites by NGF in PC12 cells (Shtukmaster, et al, 2016).…”
Section: Differentiation Of Sympathetic Neuroblasts From Nccmentioning
confidence: 99%
“…Conversely, microRNA-24 (miR-24) significantly decreased aldosterone and cortisol production by directly targeting Cyp11b1 and Cyp11b2 mRNAs (35). However, only few studies have examined the expressions and functions of miRNAs in the adrenal medulla such as microRNA-221 (miR-221) (11) and mi-croRNA-124 (miR-124) (42), which have been reported to affect the differentiation and function of PC12 cells, which are derived from a rat adrenal medullary tumor (10).…”
mentioning
confidence: 99%
“…In particular, the authors showed that miR-375 targets Sp1 , the regulator of TH and DBH, in response to stress [ 46 ]. Another study conducted by Shtukmaster and colleagues demonstrated that miR-124 is also expressed in developing sympathetic neurons and supports the maintenance of neuronal morphology in sympathoadrenal cells [ 47 ].…”
Section: The Role Of Mirnas In Nc Developmentmentioning
confidence: 95%